Persepsi kepuasan pelanggan terhadap kualiti perkhidmatan ar-Rahn : Kajian kes di Permodalan Kelantan Berhad (PKB) - Siti Zuraini, Mat Salleh (2014)
The purpose of this study was to examine the extent to which perceptions of customer satisfaction with the quality of service offered by the Ar-Rahn Permodalan Kelantan Berhad (PKB) based on demographic and six dimensions of service quality which are compliance, assurance, reliability, tangible, empathy and responsiveness. Respondents for this survey were Ar-Rahn PKB customers, Kota Bharu, and a total of 160 questionnaires were distributed by using convenience sampling technique. The design of this study is a case study survey using a quantitative approach. Questionnaires were used as an instruments for obtaining data. The data were analyzed using the Statistical Package for Social Science (SPSS) program version 20. Analysis used in this study is a descriptive analysis and inferential analysis consisting of a t-test, means test, oneway analysis of variance (ANOVA), Pearson correlation and regression. Results of the study showed that 51.9% of women customers are more satisfied using the Ar-Rahn services rather than male customer. The majority of the Ar-Rahn customers consist of those in the age group 31 to 40 years which includes 35% of the total population. Customers who has married is a majority users of the Ar-Rahn 75%. Most of Ar-Rahn customers had secondary school education level at 56.3% and entrepreneurs were the biggest users of Ar-Rahn at 35.6%. 34.4% of Ar-Rahn customers also consists of those who earn less than RM1000. Mean scores for overall dimensions of service quality and satisfaction is high. Pearson correlation test results showed that all six dimensions of service quality has a significant relationship with customer satisfaction. Regression analysis showed describe the quality of service explain 55% of the variance in customer satisfaction. Empathy factor is a critical factor while the other five dimensions is less tangible factors. In conclusion, the customers are satisfied with the quality of service provided by Ar-Rahn PKB.